Interferon α treatment of molluscum contagiosum in immunodeficiency. Issue 1 (1st January 1999) - Hourihane, Jonathan; Hodges, Elizabeth; Smith, John; Keefe, Martin; Jones, Alison; Connett, Gary
Abstract : A sister (aged 6 years) and brother (aged 8 years) presented four months apart with severe molluscum contagiosum. Both children demonstrated clinical and laboratory evidence of combined immunodeficiency. The extent of skin involvement by molluscum contagiosum precluded conventional treatment as well as intralesional interferon α (IFNα). Both subjects responded well to subcutaneous IFNα.